2018
DOI: 10.1002/pbc.27019
|View full text |Cite
|
Sign up to set email alerts
|

Fertility perspectives and priorities among male adolescents and young adults in cancer survivorship

Abstract: Infertility is a common and distressing late effect of cancer treatment among male survivors. Investigators examined desire for parenthood, prioritization of fertility compared to other life goals, and reports of fertility-related discussions among a cohort of male adolescent and young adult survivors. Eighty percent desired a biological child, yet only 31% ranked having a child among their "top 3" life goals. Only 40% reported fertility-related discussions with their health care providers in survivorship. Giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…Despite known benefits of an oncofertility program, FP rates remain low—a recent study examining fertility attitudes and parenthood goals among survivors at our institution showed that only 31% of pubertal males had banked sperm prior to therapy . Studies suggest not all at‐risk patients receive a fertility consult, but predictors of consult utilization remain unclear in pediatric oncology .…”
Section: Introductionmentioning
confidence: 99%
“…Despite known benefits of an oncofertility program, FP rates remain low—a recent study examining fertility attitudes and parenthood goals among survivors at our institution showed that only 31% of pubertal males had banked sperm prior to therapy . Studies suggest not all at‐risk patients receive a fertility consult, but predictors of consult utilization remain unclear in pediatric oncology .…”
Section: Introductionmentioning
confidence: 99%
“…Nahata et al. suggest the influence of a developmental perspective on adolescent decision making . A systematic review of FP perspectives among patients, parents, and providers supports this hypothesis .…”
mentioning
confidence: 99%
“…Notably, the mean age of survivors in this cohort was 35 years old. In Nahata et al.’s cohort, it is likely that the survivors’ relatively young age (mean = 19.5 years ± 2.6 years) strongly influenced the low priority with which they ranked fatherhood as a goal. Literature on parenting desires among childless adults in the general population has found that age and relationship formation are significant factors in the timing of childbearing goal‐adjustment .…”
mentioning
confidence: 99%
See 2 more Smart Citations